The supraspinal neural correlate of bladder cold sensation—An fMRI study - Mehnert, Ulrich (Hum Brain Mapp, 2010)
In recent years, functional imaging studies have revealed a supraspinal network, which is involved in perception and processing of bladder distention. Very little information exists on the cortical representation of C‐fiber transmitted temperature sensation of the human bladder, although C‐fibers seem to be involved in the pathomechanisms of bladder dysfunctions. Our aim was, therefore, to evaluate the outcome of bladder cold stimulation on supraspinal activity using functional magnetic resonance imaging (fMRI). A block design fMRI study was performed in 14 healthy females at the MR‐center of the University of Zurich. After catheterization, all subjects were investigated in a 3.0‐Tesla Scanner. The scanning consisted of 10 repetitive cycles. Each cycle consisted of five conditions: REST, INFUSION, SENSATION, DRAIN 1, and DRAIN 2. Cold saline was passively infused at 4–8°C during scanning. Not more than 100 ml were infused per cycle. Blood‐oxygen‐level‐dependent (BOLD) signal analysis of the different conditions was compared to REST. All activations were evaluated on a random effects level at P = 0.001. Activation of brain regions for bladder cold stimulation (DRAIN 1 period) was found bilaterally in the inferior parietal lobe [Brodmann area (BA) 40], the right insula (BA 13), the right cerebellar posterior lobe, the right middle temporal gyrus (BA 20), and the right postcentral gyrus (BA 3). In conclusion, bladder cooling caused a different supraspinal activation pattern compared to what is known to occur during bladder distention. This supports our hypothesis that cold sensation is processed differently from bladder distension at the supraspinal level. Hum Brain Mapp, 2011. © 2010 Wiley‐Liss, Inc.